Le pont-tunnel Louis-Hippolyte-La-Fontaine. Une oeuvre moderne sur les traces du passé - Atelier d'histoire de la Longue-Pointe; Charbonneau, Réjean; Dugas, Philippe; Foisy, Marie-Hélène; Laferrière, Monique; Marien, Chantal (Éditions Histoire Québec, 2007)
Keywords: Ponts; Tunnels

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

Le pont Royal-Albert, 1875-1876: histoire d'une bérézina sur fond de rivalités ferroviaires - Fougères, Dany (Revue d'histoire de l'Amérique française, 2022)
issued: 2022-24-00
Keywords: Chemins de fer; Grand Tronc; Ponts

Futur parc sur la rue Marcel-Pepin. Un lieu riche en histoire - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2020)
Number: 1
Keywords: Chemins de fer; Hôpitaux; Itinérance; Usines Angus; Variole; Épidémies

Transportons-nous, jadis! Une petite histoire du transport (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-21-00
Keywords: Automobile; Lachine (canal); Navigation; Ponts; Tramways; Transport en commun

L'histoire du chemin du Roy, XVIII-XXᵉ siècles : étude historique d'une route, d'un symbole, d'un récit - Fortin-Dupuis, Simon (Université Laval, 2024)
Keywords: Routes

L'histoire des moyens de pression des employés-es des services d'entretien des entreprises de transport en commun à Montréal, 1903-2016 - Desmarais, Jacques (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2016)
issued: 2016-23-00
Keywords: Confédération des syndicats nationaux; Transport en commun

Histoire des travaux de la Commission du Havre dans le port de Montréal - Morin, L.-E. (Le Moniteur du commerce, 1894)
Keywords: Commission du Havre; Port

Histoire du transport en commun à Montréal / History of Public Transportation in Montreal - Lajeunesse, J.-M. (Publications Apollon, 1973)
Keywords: Transport en commun

La Commission du Havre de Montréal (1850-1896) - Brouillard, Pierre (Montréal: artisans, histoire et patrimoine, 1979)
Keywords: Commission du Havre; Port

La petite histoire du CN: chronique illustrée des Chemins de fer nationaux du Canada - MacKay, Donald; Perry, Lorne (Douglas & McIntyre, 1994)
Translators: _:n32015
Keywords: Canadien National; Chemins de fer

Le transport en commun dans les villes - Linteau, Paul-André (Bâtir un pays. Histoire des travaux publics au Canada, 1988)
Keywords: Transport en commun

L'histoire du CN - MacKay, Donald (Éditions de l'Homme, 1992)
Translators: _:n32149
Keywords: Canadien National; Chemins de fer

Analyse des processus de recherche et de modélisation du patrimoine à partir de deux cas: l'écluse Saint-Gabriel du canal de Lachine et la gare Montreal and Southern Counties Railways Co. - Gosselin, Louis Pierre (Université de Sherbrooke, 2014)
Keywords: Chemins de fer; Gares; Lachine (canal); Navigation; Patrimoine

Pointe-Saint-Charles: histoire de locomotives - Bélisle, Jean (Bulletin de l'Association québécoise pour le patrimoine industriel, 2012)
issued: 2012-21-00
Keywords: Canadien National; Chemins de fer; Grand Tronc

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

L'empire invisible: histoire des télécommunications au Canada. Volume 1: 1846 à 1956 - Rens, Jean-Guy (Presses de l'Université du Québec, 1993)
Keywords: Bell Canada; Téléphone

L'empire invisible: histoire des télécommunications au Canada. Volume 2: 1956 à nos jours - Rens, Jean-Guy (Presses de l'Université du Québec, 1993)
Keywords: Bell Canada; Téléphone

L'aéroport de Saint-Hubert, 1927-1941 - Caradot, Rémi (Éditions Histoire Québec, 2005)
Keywords: Aéroport

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

Montréal et la catastrophe du pont ferroviaire de Beloeil - Saint-Jacques, Roger (Les cahiers d'histoire de la Société d'histoire de Beloeil, 1985)
Keywords: Chemins de fer; Ponts

Montréal et les débuts de la navigation à vapeur sur le St-Laurent - Dubuc, Alfred (Revue d'histoire économique et sociale, 1967)
Number: 1
Keywords: Molson (famille); Navigation

Le Pont Victoria. Le lien vital - Kennell, Elizabeth H. (Montréal, une histoire à suivre, 1992)
Translators: _:n34924
Keywords: Ponts; Victoria (pont)

Travaux d'aménagement du Havre de Montréal 1830-1850 (étude préliminaire) (Groupe de recherche sur l'histoire du port de Montréal, 1982)
Keywords: Port

Construction des élévateurs à grain du port de Montréal 1885-1970 - Conter, Alan (Groupe de recherche sur l'histoire du port de Montréal, 1981)
Keywords: Blé; Céréales; Port; Élévateurs à grain

Les réseaux des «lyriques» et des «veillées»: une histoire de la chanson au Québec dans l'entre-deux-guerres par la radiodiffusion au poste CKAC de Montréal (1922-1939) - Bellemare, Luc (Université Laval, 2012)
Keywords: CKAC; Chanson; Radio

The Development of Canada's Five Leading National Ports - Forward, Charles N. (Urban History Review / Revue d'histoire urbaine, 1982)
Number: 3
Keywords: Port

L'automobile et l'expansion des banlieues: le cas de Montréal, 1901-2001 - Bussiere, Yves (Urban History Review / Revue d'histoire urbaine, 1989)
Number: 2
Keywords: Automobile; Banlieue

Les banlieues de l'immigration ou quand les immigrants refont les banlieues - Germain, Annick; Rose, Damaris; Richard, Myriam (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Italiens; Mile End; Mobilité résidentielle; Parc-Extension (quartier); Petite-Italie (quartier); Quartiers; Saint-Léonard

Montréal 1950-2010: la métamorphose de l'économie spatiale - Shearmur, Richard (Histoire de Montréal et de sa région, 2012)
Keywords: Autoroutes; Centres commerciaux; Commerce de détail; Navettage; Travail

L'expansion métropolitaine: vers une polycentricité assumée - Sénécal, Gilles; Vachon, Nathalie (Histoire de Montréal et de sa région, 2012)
Keywords: Autoroutes; Banlieue; Centres commerciaux; Mobilité résidentielle; Métropole

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Une île sans partage: la domination de Montréal à l'ère d'une nouvelle dynamique insulaire - Fougères, Dany; Shaffer, Valérie (Histoire de Montréal et de sa région, 2012)
Keywords: Automobile; Banlieue; Centre-ville; Hôtel de ville; Maires; Ponts; Quartiers; Routes; Réformistes; Tramways; Vieux-Montréal

Le Pont Victoria, un lien vital / Victoria Bridge, the vital link - Triggs, Stanley (Musée McCord d'histoire canadienne, 1992)
Keywords: Ponts; Victoria (pont)

Le Pont / The Bridge - Triggs, Stanley G. (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

Le Cadre / The Setting - Young, Brian (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

L'inauguration / The Celebration - Graham, Conrad (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

L'impact / The Impact - Lauzon, Gilles (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

Le Québec, Montréal, Ottawa et Occidental: une entreprise d'État, 1875-1882 - Stewart, Michel (Université Laval, 1984)
Keywords: Chemins de fer

Les débuts de la radio à Montréal et le poste C.K.A.C - Montigny, Bernard (Université de Montréal, 1979)
Keywords: CKAC; Radio

Le développement du port de Montréal, 1850-1896 - Brouillard, Pierre (Université du Québec à Montréal, 1976)
Keywords: Port

La participation canadienne au programme impérial de transfert par dirigeables 1924-1931 - Fortier, Rénald (Université de Sherbrooke, 1982)

La compagnie de chemin de fer du Saint-Laurent et de l'Atlantique (1835-1853) - Cadieux, Hélène (Université de Sherbrooke, 1991)
Keywords: Chemins de fer

The Construction of the First Lachine Canal, 1815-1826 - Tulchinsky, Gerald (Université McGill, 1960)
Keywords: Lachine (canal); Navigation

L'encadrement juridique des infrastructures et des services publics urbains: le cas du transport en commun à Montréal, 1860-1880 - Fougères, Dany (Université du Québec à Montréal, 1991)
Keywords: Tramways; Transport en commun

" Du chemin qui marche " au chemin du Roy à la Pointe-aux-Trembles - Desjardins, Pierre (Histoire Québec, 2010)
Number: 2
Keywords: Navigation; Pointe-aux-Trembles; Routes; Voirie

"Un nouveau chapitre de l’aviation canadienne s’ouvrira-t-il à Dorval?" – Bernard W. Sznycer, Selma G. Gottlieb et l’Intercity SG-VI - Fortier, Rénald (Histoire Québec, 2016)
Number: 3
Keywords: Avionnerie; Ingénieurs

Le pont Jacques-Cartier - Giroux, Éric (Histoire Québec, 2010)
Number: 2
Keywords: Ponts

The Montreal & Southern Counties Railway Company (1909-1956) - Grumley, J. R. Thomas (Histoire Québec, 2010)
Number: 1
Keywords: Chemins de fer

Deux ponts à ne pas confondre: Honoré-Mercier et Saint-Laurent - Gravel, Denis (Histoire Québec, 2010)
Number: 2
Keywords: Canadien Pacifique; Chemins de fer; Ponts

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Number: 4
Keywords: Lachine (canal); Paysages

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Number: 3
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Le chemin de fer sur la glace - Lefort, Pierre (Histoire Québec, 2000)
Number: 1
Keywords: Canadien Pacifique; Chemins de fer; Longueuil; Ponts; Victoria (pont)

Le pont tubulaire et ferroviaire Victoria - Pratt, Michel (Histoire Québec, 2010)
Number: 1
Keywords: Chemins de fer; Ponts; Victoria (pont)

Effervescence dans les musées: la stratégie de communication externe des musées montréalais: une recherche exploratoire - Navarre, Audrey (Université du Québec à Montréal, 1992)
Keywords: Musées

L’ère des archives québécoises sur le Web - Robert, Mario (Cap-aux-Diamants, 2014)
issued: 2014-24-00
Keywords: Archives; Archives municipales

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers

Atlantic Iconography: Images of the St Lawrence-Clyde Passengers Liners of the Canadian Pacific Railway. - Stevenson, Iain (Montreal-Glasgow, 2005)
Keywords: Canadien Pacifique; Chemins de fer

Paradoxe patrimonial: le pont-tunnel Louis-Hippolyte-La Fontaine et le village de Longue-Pointe - Cayouette-Ashby, Eve-Lyne (Bulletin de l'Association québécoise pour le patrimoine industriel, 2007)
issued: 2007-21-00
Keywords: Longue-Pointe; Ponts; Saint-François-d'Assise (paroisse)

ABBOTT, JOB - McNally, Larry (Dictionnaire biographique du Canada, 1990)

''L'autoroute est-ouest, c'est pas le progrès!'': environnement et mobilisation citoyenne en opposition au projet d'autoroute est-ouest à Montréal en 1971 - Poirier, Valérie (Bulletin d'histoire politique, 2015)
issued: 2015-24-00
Keywords: Autoroutes; Groupes populaires

''Vive la vélorution!'': Le Monde à bicyclette et les origines du mouvement cycliste à Montréal, 1975-1980 - Ross, Daniel (Bulletin d'histoire politique, 2015)
issued: 2015-24-00
Keywords: Cyclisme; Groupes populaires

Montréal portuaire et ferroviaire : actes du 5e congrès de l'Association québécoise pour le patrimoine industriel, Montréal, 8 et 9 mai 1992 - Association québécoise pour le patrimoine industriel (L'Association, 1993)
Keywords: Chemins de fer; Port

Le Saint-Laurent, comme une rue principale - Franck, Alain (Continuité, 2001)
issued: 2001-22-00
Keywords: Navigation; Voie maritime

FLEMING, JOHN - Deslauriers, Peter (Dictionnaire biographique du Canada, 1987)

Les chantiers navals du canal Lachine - Corbel, Nadine H. J. (Université Concordia, 1991)
Keywords: Construction navale; Navigation

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Leméac, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

Le téléphone dans une grande ville industrielle nord-américaine: Montréal, 1880-1930 - Poitras, Claire (Les Cahiers, Télécommunications, Histoire et Société, 1997)
Keywords: Bell Canada; Téléphone

Little Burgundy: The Interwoven Histories of Race, Residence, and Work in Twentieth-Century Montreal - High, Steven (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-23-00
Keywords: Chemins de fer; Noirs; Petite-Bourgogne; Quartiers; Travail

Urban Environments and the Animal Nuisance: Domestic Livestock Regulation in Nineteenth-Century Canadian Cities - Kheraj, Sean (Urban History Review / Revue d'histoire urbaine, 2015)
issued: 2015-23-00/2016-21-00

Les services urbains sous surveillance politique: le pouvoir municipal et l'établissement du service de transport en commun à Montréal, 1860-1880 - Fougères, Dany (Urban History Review / Revue d'histoire urbaine, 1997)
Number: 1
Keywords: Transport en commun

Penser la mobilité, penser Montréal. La planification du tracé du réseau initial de métro, 1960-1966 - Gilbert, Dale (Revue d'histoire de l'Amérique française, 2014)
issued: 2014-22-00/2014-23-00
Keywords: Transport en commun

Automobile, transports urbains et mutations: l’automobilisation urbaine de Québec, 1919–1939 - Faugier, Étienne (Urban History Review / Revue d'histoire urbaine, 2009)
issued: 2009-23-00
Keywords: Automobile

La "Normandie du Nouveau Monde": la société Canada Steamship Lines, l’antimodernisme et la promotion du Québec ancien - Murton, James (Revue d'histoire de l'Amérique française, 2001)
Cette étude tend à montrer que durant les années 1930 la Canada Steamship Lines (CSL) a créé et disséminé une image du Québec comme société simple, prémoderne et rurale, dans le but d’accroître la clientèle de ses navires de croisière et de ses hôtels. On y examine les documents publicitaires de la compagnie et l’on montre qu’elle faisait aussi appel à d’autres individus pour construire cette image. L’anthropologue et folkloriste Marius Barbeau a écrit un ouvrage pour le compte de la CSL et celle-ci s’est associée au gouvernement du Québec pour promouvoir le renouveau artisanal. Ces divers acteurs partageaient la croyance antimoderne dans l’existence d’un Québécois vrai, authentique et qui constituait le coeur même de la nation : l’« Habitant ».
issued: 2001-22-00
Keywords: Navigation

Politics of Transportation Services in Suburban Montreal: Sorting Out the "Mile End Muddle", 1893-1909 - Boone, Christopher (Urban History Review / Revue d'histoire urbaine, 1996)
Number: 2
Keywords: Mile End; Tramways; Transport en commun

L’émeute des tramways de Montréal (1955) et la mauvaise conduite des étudiants: un cas d’appropriation de l’espace urbain - Poitras, Daniel (Urban History Review / Revue d'histoire urbaine, 2018)
issued: 2018-23-00/2019-21-00
Keywords: Association générale des étudiants de l'Université de Montréal; Associations étudiantes; Délinquance; Tramways; Transport en commun; Université McGill; Université de Montréal; Émeutes; Étudiants

Les traverses entre Saint-Vincent-de-Paul et le Sault-au-Récollet - Forget, André (Cahiers d'histoire du Sault-au-Récollet, 1992)
issued: 1992-23-00
Keywords: Ponts; Saint-Vincent-de-Paul (paroisse); Sault-au-Récollet

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Montréal, par ponts et traverses - Wilson, Pierre; Poussart, Annick (Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 1999)
Keywords: Ponts

Montréal, by Bridge and Crossing - Wilson, Pierre; Poussart, Annick (Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 1999)
Keywords: Ponts

"Du châssis à la machine à mouler": transformation des méthodes de production dans l'industrie canadienne du moulage, au cours de la seconde moitié du XIXe siècle - Bischoff, Peter (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Number: 1
Keywords: Mouleurs

Le Plateau au temps de la guerre (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
issued: 2015-23-00
Keywords: Conscription; Femmes; Fusiliers Mont-Royal; Gares; Guerre; Houde; Camillien; Juifs; Maires; Plateau Mont-Royal; Quartiers; Roman; Tramways; Transport en commun

Le Plateau sur ses grands chevaux (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
issued: 2016-22-00
Keywords: Chasse à courre; Chevaux; Clubs; Montreal Hunt Club; Tramways; Transport en commun

Tourner à droite, virer à gauche. Le Plateau politique (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
issued: 2016-21-00
Keywords: Beaubien; Louis; Bethune; Norman; Chemins de fer; Communistes; Confection; Conseillers municipaux; Députés; Femmes; Gares; Grèves; Juifs; Mile End; Médecine; Partis politiques; Plateau Mont-Royal; Quartiers; Rose; Fred; Syndicats internationaux; Travail; Union internationale des ouvriers du vêtement pour dames; Élections

Soutien et entraide. Les mouvements coopératifs et communautaires du Plateau de 1970 à 2000 (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Clinique des citoyens de Saint-Jacques; Cyclisme; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

John Elsdale Molson contre le chemin de fer Grand Tronc - Bur, Justin (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Chemins de fer; Grand Tronc; Rosemont

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 6
Keywords: Incendies; Routes; Rues

Les quatre saisons d'Ahuntsic - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Ahuntsic; Gares; Quartiers; Toponymie; Tramways; Transport en commun

Une culture du voyage. Chronique d'une maisonnée d'Ahuntsic (1925-1945) - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 5
Keywords: Automobile; Famille

Retrouver les lieux de passages - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Ponts; Rivière des Prairies; Sault-au-Récollet

À travers le pare-brise: la création des territoires touristiques à l’ère de l’automobile (Québec et Ontario, 1920-1967) - Lambert, Maude-Emmanuelle (Université de Montréal, 2013)
Keywords: Automobile; Tourisme

Un cas d'ethnologie appliquée: la technique de communication mise au point par Bell Canada pour les sourds - Amédée, Alourdes (Université Laval, 1995)
Keywords: Bell Canada; Téléphone

Terminus ferroviaires et espace urbain: le Canadien Pacifique et la transformation de l'est de Montréal, 1870-1915 - Duchesne, Julie (Université du Québec à Montréal, 2003)
Keywords: Canadien Pacifique; Chemins de fer

The North-Shore railways: a Study of the Montreal Colonization Railroad and the North Shore Railway, 1854-1885 - Young, Brian (Queen's University, 1972)
Keywords: Canadien Pacifique; Chemins de fer; Grand Tronc

Le Drummond County Railway: 1886-1900 - Blais, Ghislain (Université Laval, 2006)
Keywords: Chemins de fer

La motorisation ou "La rançon du progrès". Tramways, véhicules-moteurs et circulation (Montréal, 1900-1930) - Veilleux, Denis (Université McGill, 1998)
Keywords: Automobile; Tramways; Transport en commun

Émergence du réseau Internet au Québec: une approche centrée sur les acteurs - Brosseau, Benoît (Université du Québec à Montréal, 2004)
Keywords: Internet

Le premier chemin royal de Québec à Montréal sur la rive nord du fleuve Saint-Laurent - Sanfaçon, Roland (Université Laval, 1956)
Keywords: Routes

Le développement du réseau pionnier des chemins de fer au Canada: isolement et intégration (1836-1883) - Lemaire, Marc (Université de Montréal, 1997)
Keywords: Chemins de fer

Une vie de débardeur: troubles et changements au port de Montréal (1960-1975) - Martel, Étienne (Université du Québec à Montréal, 2014)
Keywords: Port

Le choix du tout-à-l'automobile (1953-1967): un contexte propice à l'aménagement de l'échangeur Turcot - Wolford, Alexandre (Université de Montréal, 2015)
Keywords: Automobile; Autoroutes; Voirie

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

Savoirs, mobilisations et construction du risque environnemental de l'automobile durant les long sixties à Montréal - Poirier, Valérie (Université du Québec à Montréal, 2018)
Keywords: Automobile; Groupes populaires; Pollution

À la croisée des chemins : mise en place et implantation du réseau de télégraphe électrique canadien, 1846-1867 - Dumais-Gingras, Pierre (Université du Québec à Montréal, 2021)
Keywords: Téléphone

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

Le pont-tunnel Louis-Hippolyte-La Fontaine : aux origines d'une infrastructure routière régionale - Gaudry, William (Université du Québec à Montréal, 2022)
Keywords: Autoroutes; Ponts; Tunnels

Montréal en 1919 : industries, travail et espaces résidentiels - Girard, David (Université du Québec à Montréal, 2020)
Keywords: Tramways; Travail

Les bus de Verdun (I) - Clairoux, Benoît (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 3
Keywords: Autobus; Quartiers; Transport en commun; Verdun

Les bus de Verdun (II) - Clairoux, Benoît (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 4
Keywords: Autobus; Quartiers; Transport en commun; Verdun

Au temps des chevaux et des rails (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2014)
issued: 2014-22-00
Keywords: Automobile; Chemins de fer; Chevaux; Cyclisme; Funiculaire; Gares; Groupes populaires; Mont Royal; Plateau Mont-Royal; Quartiers; Tramways; Transport en commun

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-23-00
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Translators: _:n117 Translators: _:n62493
Keywords: Métropole; Port

Le Conseil des métiers et du travail de Montréal (CMTM) et la question de la municipalisation des Tramways de 1900 à 1930 - Lessard, Jonathan (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2004)
issued: 2004-23-00
Keywords: Conseil des métiers et du travail de Montréal; Tramways

Le Conseil des métiers et du travail à Montréal et le transport en commun, 1899-1930 - Gaudry, William (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2012)
issued: 2012-23-00
Keywords: Conseil des métiers et du travail de Montréal; Transport en commun

Une vie de débardeur: troubles et changements au port de Montréal (1960-1975) - Martel, Étienne (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2013)
issued: 2013-23-00
Keywords: Port

Une vie de débardeur: luttes syndicales au port de Montréal, 1960-1975 - Martel, Étienne (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2014)
issued: 2014-21-00
Keywords: Port

The Montreal Metro: Integration of Art and Architecture - Cantieni, Graham (Université Concordia, 1987)
Keywords: Transport en commun

Les grandes gares ferroviaires du Québec: 1888-1945 - Delli-Colli, Vittoria (Université Laval, 2009)
Keywords: Chemins de fer; Gares

Bruce Price, and his Montreal Train Stations - Dandurand, Kevin (Université Concordia, 2000)
Keywords: Gare Viger; Gare Windsor; Gares

Railway Politics in Montreal, 1867-1878 - Young, Brian J. (CHA / SHC, Historical Papers / Communications historiques, 1972)
Keywords: Chemins de fer

Le développement du port de Montréal au début du 20e siècle - Linteau, Paul-André (CHA / SHC, Historical Papers / Communications historiques, 1972)
Keywords: Port

Le port de Montréal à la veille de l'ouverture de la nouvelle voie navigable du Saint-Laurent - Camu, Pierre (Cahiers de géographie du Québec, 1958)
issued: 1958-10/1959-03
Keywords: Navigation; Port; Voie maritime

The St. Lawrence Ship Channel, 1805-1865 - Corley, Nora T. (Cahiers de géographie du Québec, 1967)
Number: 23
Keywords: Navigation

Montréal, centre de décisions maritimes - Camu, Pierre (Cahiers de géographie du Québec, 1983)
Number: 71
Keywords: Navigation; Port

Les autoroutes et le commerce interurbain dans la région de Montréal - Massicotte, Benoît (Cahiers de géographie du Québec, 1983)
Number: 71
Keywords: Autoroutes

The Process of Hydraulic Industrialization on the Lachine Canal, 1840-1880: Origins, Rise and Fall - Willis, John (Environnement Canada, Service canadien des Parcs, 1987)
Keywords: Lachine (canal); Énergie hydraulique

De la voile à la vapeur: la construction des navires dans les environs de Québec et de Montréal / From Sail to Steam (...) - Baker, Victoria A.; Dutton, Diana (Musée Marsil de Saint-Lambert / Marsil Museum of Saint-Lambert, 1982)
Keywords: Construction navale; Navigation

The Application of Steam Navigation to the St. Lawrence 1809-1840 - Wilson, George H. (Université McGill, 1961)
Keywords: Navigation; Énergie hydraulique

Le Canal de Lachine jusqu'en 1870: origine et fonction d'un canal hydraulique - Willis, John (History and Technology, 1986)
Number: 4
Keywords: Lachine (canal); Énergie hydraulique

Canadian National Railways. Vol. I. Sixty Years of Trial and Error 1836-1896 - Stevens, George Roy (Clarke, Irwin, 1960)
Keywords: Canadien National; Chemins de fer; Grand Tronc

The Lachine Canal, 1840-1900: Preliminary Report - Willis, John (Parcs Canada, 1983)
Keywords: Lachine (canal)

Le Canal Lachine jusqu'en 1870: origine et fonction d'un canal hydraulique - Willis, John (Traditions maritimes au Québec, 1985)
Keywords: Lachine (canal); Énergie hydraulique

Le Saint-Laurent. Grande porte de l'Amérique - Lasserre, Jean-Claude (Hurtubise HMH, 1980)
Keywords: Navigation; Voie maritime

Les voyages vers 1800 - Tessier, Albert (Les Cahiers des Dix, 1941)

Montréal, notre île - Les passages d'eau à la fin du XVIIIe siècle - Faribault-Beauregard, Marthe (Montréal: activités, habitants, quartiers, 1984)
Keywords: Bacs

Original Acquisition of Land in Montreal by the Grand Trunk Railway of Canada - Hoskins, F. H. (Université Mc Gill, Département de géographie, 1987)
Keywords: Grand Tronc; Pointe-Saint-Charles; Quartiers

John Richardson et la construction du canal de Lachine - Laliberté, Pierre (Cahier de la Société historique de Montréal, 1983)
issued: 1983-03/1983-06
Keywords: Lachine (canal); Navigation; Richardson; John

Montréal et les débuts de la navigation à vapeur sur le Saint-Laurent - Dubuc, Alfred (La grande mouvance, 1990)
Keywords: Molson (famille); Navigation; Voie maritime

The Montreal Ship Channel, 1805-1865 - Corley, Nora (Université McGill, 1961)
Keywords: Navigation

L'avènement du premier chemin de fer au Canada: St-Jean-Laprairie, 1836 - Cinq-Mars, François (Mille Roches, 1986)
Keywords: Champlain and St. Lawrence Railroad; Chemins de fer

La navigation à vapeur sur le Saint-Laurent - Baker, Victoria A. (De la voile à la vapeur: la construction de navires dans les environs de Québec et de Montréal / From Sail to Steam (...), 1982)
Keywords: Navigation; Port; Voie maritime

A History of the Grand Trunk Railway of Canada - Brown, Thomas Storrow (Hunter, Rose, 1864)
Keywords: Chemins de fer; Grand Tronc

Canal de Lachine: atlas historique / Lachine Canal: Historic Atlas - Bergeron, Diane; Bougie, Luc; Pineault, Danielle; Lépine, Luc (Parcs Canada, 1983)
Keywords: Cartes et plans; Lachine (canal)

1836-1986, a Tribute to Canada's First Railway on its Sesquincentenial (Canadian Railroad Historical Association, 1986)
Keywords: Champlain and St. Lawrence Railroad; Chemins de fer

Suburban Street Railway Strategies in Montreal, Toronto, and Vancouver, 1896-1930 - Armstrong, Christopher; Nelles, H. V. (Power and Place: Canadian Urban Development in the North American Context, 1986)
Keywords: Banlieue; Tramways

La politique urbaine: fondements théoriques et application pratique: analyse du projet d'autoroute est-ouest à Montréal - Delorme, Pierre (Université d'Ottawa, 1976)
Keywords: Autoroutes; Voirie

Contradictions urbaines et analyse politique: une étude du projet de construction de l'autoroute Est-Ouest à Montréal - Delorme, Pierre (Le système politique de Montréal, 1986)
Keywords: Autoroutes; Voirie

La réduction de gaz à effet de serre et les transports urbains des personnes à Montréal - Gandulfo, Mónica (Université de Sherbrooke, 2000)
Keywords: Automobile; Climat; Transport en commun

We Built Canada. Donald Smith and the Canadian Pacific Railway - Wilson, Keith (The Book Society of Canada, 1978)
Keywords: Canadien Pacifique; Chemins de fer; Smith; Donald

Promoters and Politicians: The North-Shore Railways in the History of Quebec, 1854-1885 - Young, Brian J. (University of Toronto Press, 1978)
Keywords: Chemins de fer

The Port of Montreal - Tombs, Laurence Chalmers (Université McGill, 1926)
Keywords: Port

The Harbour of Montreal, an Address to the St. James Literary Society of Montreal - Tombs, G. (s.é., 1952)
Keywords: Port

National Problems of Canada; the Port of Montreal - Tombs, Laurence Chalmers (Macmillan, 1926)
Keywords: Port

Le transport urbain à Montréal, 1861-1961 (Commission de transport, 1961)
Keywords: Tramways; Transport en commun

Les flux de transport par autobus entre Montréal et sa région - Villeneuve, Paul; Delphanque, France; Roy, Jacques (Revue de Géographie de Montréal, 1974)
Number: 3
Keywords: Autobus; Transport en commun

Recent Developments in the Grain Trade of the Port of Montreal - Slack, Brian (Revue de Géographie de Montréal, 1964)
Number: 2
Keywords: Port

Canadian National Railways. Vol.II. Toward the Inevitable, 1896-1922 - Stevens, George Roy (Clarke, Irwin, 1962)
Keywords: Canadien National; Chemins de fer; Grand Tronc

The Port of Montreal - Slack, Brian (Montreal Geographical Essays, 1981)
Keywords: Port

The Impact of the St. Lawrence Seaway on the Port of Montreal - Slack, Brian (Université McGill, 1963)
Keywords: Navigation; Port; Voie maritime

Montreal's Streetcars, 1892-1959; A Brief Look at 67 Years of Electric Tramway Operation in Montreal, on the Occasion of Montreal Transportation Commission's Historical Pageant Marking the End of Tramway Service (Canadian Railroad Historical Ass., 1959)
Keywords: Tramways

Montreal Port Annual. Centenary Souvenir and Reference 100 Years of Progress (Shipping Register, 1930)
Keywords: Port

Urban Transit in Montreal: The Last Hundred Years, 1861-1961 - Montreal Urban Community Transit Commission (The Commission, 1970)
Keywords: Autobus; Tramways; Transport en commun

Canada and the Grand Trunk, 1829-1924: The Genesis of Railway Construction in British America and the Story of The Grand Trunk Railway Company of Canada from its Inception to its Acquisition by Canada - Lovett, H.A. (s.é., 1927)
Keywords: Chemins de fer; Grand Tronc

The Romance of the Canadian Pacific Railway - Macbeth, Roderick George (Ryerson Press, 1924)
Keywords: Canadien Pacifique; Chemins de fer

Urban Mass Transit - Linteau, Paul-André (Building Canada. A History of Public Works, 1988)
Keywords: Transport en commun

Van Horne's Road - Lavallée, Omer S. A. (Fitzhenry & Whiteside, 1975)
Keywords: Canadien Pacifique; Chemins de fer

The Montreal City Passenger Railway Company - Lavallée, Omer S. A. (Canadian Railroad Historical Association, 1961)
Keywords: Montreal City Passenger Railway Company; Tramways

A History of the Canadian Pacific Railway - Innis, Harold Adams (Buffalo, University of Toronto Press, 1971)
Keywords: Canadien Pacifique; Chemins de fer

History of the Canadian Pacific Railway - Lamb, William Kaye (Macmillan/Collier Macmillan, 1977)
Keywords: Canadien Pacifique; Chemins de fer

Terminus Craig - Murphy, M. Peter (Canadian Rail, 1973)
Keywords: Tramways

Un cadre analytique pour étudier l'impact économique des autoroutes interurbaines: une application à la région de Montréal - Polese, Mario; Thibodeau, Jean-Claude (L'Actualité économique, 1975)
issued: 1975-07/1975-09
Keywords: Autoroutes; Voirie

Montreal's Last Trolleys - Latour, Denis (Canadian Rail, 1977)
Keywords: Tramways

Le système urbain / The Urban System - Greer-Wootten, Bryn; Marshall, John V. (Montréal. Guide d'excursions / Field Guide, 1972)

Le port de Montréal, 1914-1940 - Laforest, M. (École des hautes études commerciales, 1942)
Keywords: Port

The Development of the Port of Montreal - Gosling, S. M. (University of Reading, 1932)
Keywords: Port

L'aéroport international de Montréal - Garry, Robert (Revue de Géographie de Montréal, 1967)
Number: 1
Keywords: Aéroport; Dorval

La fonction commerciale du port de Montréal depuis 1946 - Gagnon, Albert (École des Hautes études commerciales, 1963)
Keywords: Port

Rates of Return in Railway Investment and Implications for Government Subsidization of the Canadian Pacific Railway: Some Preliminary Results - George, Peter J. (Perspectives on Canadian Economic History, 1987)
Keywords: Canadien Pacifique; Chemins de fer

The Railways of Montreal - Frost, David B. (Montreal Geographical Essays, 1981)
Keywords: Chemins de fer

Urbanisation et réseau de transport dans la région montréalaise (1945-1975) - Dumont, Francine; Labonté, Pierre (Office de planification et de développement du Québec, 1977)

Transportation Problems in Canada and Montreal Harbour - Cowie, F. W. (Institute of Civil Engineers, 1914)
Keywords: Port

Ironie du char: un essai sur l'automobile et la crise des transports à Montréal - Dagenais, Jean-Pierre (J.-P. Dagenais, 1982)
Keywords: Automobile

L'auto et la crise des transports à Montréal, de 1900 à 1981 - Dagenais, Jean-Pierre (Université du Québec à Montréal, 1984)
Keywords: Automobile

The Grand Trunk Railway of Canada - Currie, A. W. (University of Toronto Press, 1957)
Keywords: Chemins de fer; Grand Tronc

The Mount Royal Tunnel; Canada's First Subway - Clegg, Anthony (Trains and Trolleys Book Club, 1963)
Keywords: Chemins de fer; Tunnels

The CPR. A Century of Corporate Welfare - Chodos, Robert (James Lewis and Samuel, 1973)
Keywords: Canadien Pacifique; Chemins de fer

The Great National Port of Canada: Features of the Important Extension Works in Progress in Montreal Harbour - Cowie, F. W. (Canadian Engineer, 1911)
Keywords: Port

Le port et les transports - Brouillette, Benoît (Montréal économique, 1943)
Keywords: Port

Le port de Vancouver (comparé au port de Montréal) - Brouillette, Benoît (L'Actualité économique, 1953)
Keywords: Port

Le port de Montréal, hier et aujourd'hui - Brouillette, Benoît (Revue de Géographie de Montréal, 1967)
Number: 2
Keywords: Port

Evolution du trafic dans la voie maritime du Saint-Laurent - Camu, Pierre (Revue de Géographie de Montréal, 1964)
Number: 2
Keywords: Navigation; Voie maritime

Notre milieu: Montréal économique IV. Le port et les transports - Brouillette, Benoît (L'Actualité économique, 1943)
Number: 3
Keywords: Port

Canadian Marconi: CFCF the Forgotten First - Godfrey, Donald G. (Canadian Journal of Communication, 1982)
Number: 4
Keywords: CFCF; Canadian Marconi; Radio

Hunter's Hand-Book of the Victoria Bridge... A Brief History of that Wonderful Work - Boxer, F. N. (Hunter, 1860)
Keywords: Chemins de fer; Grand Tronc; Ponts; Victoria (pont)

Montreal and the Inauguration of Trans-Canada Transportation - Bonar, J. C. (s.é., 1936)
Keywords: Chemins de fer

Montreal's Electric Streetcars. An Illustrated History of the Tramway Era, 1892 to 1959 - Binns, Richard M. (Railfare Enterprise, 1973)
Keywords: Tramways

The Last Spike. The Great Railway 1881-1885 - Berton, Pierre (McClelland & Stewart, 1971)
Keywords: Canadien Pacifique; Chemins de fer

Souvenirs de nos p'tits chars - Angus, Fred F. (Association historique canadienne du chemin de fer, 1971)
Keywords: Tramways

Le Grand Défi. Le chemin de fer canadien - Berton, Pierre (Editions du Jour, 1975)
Keywords: Canadien Pacifique; Chemins de fer

The National Dream. The Great Railway 1871-1881 - Berton, Pierre (Montréal, McClelland and Stewart, 1970)
Keywords: Canadien Pacifique; Chemins de fer

Le Grand Défi. Le chemin de fer canadien. Le dernier mille - Berton, Pierre (Edition du Jour, 1975)
Keywords: Canadien Pacifique; Chemins de fer

Ravenscrag: the Allan Royal Mail Line - Appleton, Thomas E. (McClelland and Stewart, 1974)
Keywords: Allan Royal Mail Line; Allan; Andrew; Allan; Hugh; Navigation

Toussaint Trudeau, 1826-1893 - Audet, Francis-J. (Bulletin des recherches historiques, 1941)
Keywords: Chemins de fer; Ingénieurs; Trudeau; Toussaint

Montreal Street Railway's 790 Class Cars - Binns, Richard M. (Canadian Rail, 1962)
Keywords: Tramways

Snow-Fighting on the Transit Lines of Montreal - Binns, Richard M. (Canadian Rail, 1963)
Keywords: Tramways

Montreal Streetcars: 638 Class the Scotch Cars - Binns, Richard M. (Canadian Rail, 1964)
Keywords: Tramways

The Grey Cars - Binns, Richard M. (Canadian Rail, 1967)
Keywords: Tramways

War Time Cars - Binns, Richard M. (Canadian Rail, 1967)
Keywords: Tramways

Street Cars Up Mount Royal - Binns, Richard M. (Canadian Rail, 1980)
Keywords: Tramways

The Montreal & Lachine Rail Road and its Successors - Bales, Robert G. (Canadian Rail, 1966)
Keywords: Chemins de fer; Montreal and Lachine Rail Road

Le Canal Lachine sous le régime français - Bonin, R. (Bulletin des recherches historiques, 1936)
Number: 5
Keywords: Lachine (canal)

Le port de Montréal - Brouillette, Benoît (L'Actualité économique, 1935)
Number: 2
Keywords: Port

L'avenir du port de Montréal en corrélation avec divers facteurs de l'économie générale du Canada - D'Hauteserve, Louis (L'Actualité économique, 1927)
Number: 2
Keywords: Port

L'offre en transport et les changements d'utilisation fonctionnelle du sol à Montréal entre 1964 et 1983 - Rodrigue, Jean-Paul (Cahiers de géographie du Québec, 1990)
Number: 94

Angus Shops of the Canadian Pacific Railway - Elson, Harvey W. (Canadian Rail, 1977)
Keywords: Canadien Pacifique; Chemins de fer; Usines Angus

The Farm on chemin Vervais!, 1913-1963 - Pharand, Jacques (Canadian Rail, 1975)
Keywords: Tramways

Man Conquers Mountain - a History of Montreal's Mountain Park Railway - Mason, Phillips (Canadian Rail, 1969)
Keywords: Funiculaire

MTC's 1900 Class One Man Cars - Binns, Richard M. (Canadian Rail, 1967)
Keywords: Tramways

Les petits chars de Montréal - Where Are they Now? - Murphy, M. Peter (Canadian Rail, 1973)
Keywords: Tramways

The Inter-City Cars of the MP & IR - Pharand, Jacques (Canadian Rail, 1974)
Keywords: Tramways

Train 255 Departs Windsor Station as CP Rail's Last Passenger Unit - Lavallée, Omer S. A. (Canadian Rail, 1983)
issued: 1983-01/1983-02
Keywords: Canadien Pacifique; Chemins de fer

Black Cars - Binns, Richard M. (Canadian Rail, 1966)
Keywords: Tramways

Windsor Station 1889-1964 - Lavallée, Omer S. A. (Canadian Rail, 1964)
Keywords: Chemins de fer; Gare Windsor

Donald H. Beatty of the C.P.R.: A Biography - Miller-Barstow, Donald Hughes (McClelland et Stewart, 1951)
Keywords: Beatty; Edward Wentworth; Canadien Pacifique; Chemins de fer

Québec en Amérique au XIXe siècle. Essai sur les caractères économiques de la laurentie - Faucher, Albert (Fides, 1973)
Keywords: Port

Canadian Pacific: A Brief History - McDOUGALL, J. Lorne (McGill University Press, 1968)
Keywords: Canadien Pacifique; Chemins de fer

Billet d'omnibus - Massicotte, E.-Z. (Bulletin des recherches historiques, 1929)
Number: 6
Keywords: Transport en commun

The Port of Montreal: Its History and Development - Cowie, F. W. (Shipping Register, 1925)
Number: 12
Keywords: Port

Dundee-Built Locomotive in Canada's First Railways - Lavallée, Omer S. A. (Railroad History, 1983)
issued: 1983-23-00
Keywords: Chemins de fer

The Lachine Canal - Cureton, Edward A. (Université McGill, 1957)
Keywords: Lachine (canal); Navigation

P.A.Y.E. 80: a Montreal Invention, 1905-1985 - Angus, Fred F. (Canadian Rail, 1985)
issued: 1985-05/1981-06
Keywords: Tramways

A Brief History of the Montreal Street Railway Company From 1861 to 1910 (Annual Report of the Montreal Street Railway Company For the Fiscal Year Ended 30th September 1910, 1910)
Keywords: Montreal Street Railway Company; Tramways

Meighen and the Montreal Tycoons: Railway Policy in the Election of 1921 - Graham, W. Roger (CHA / SHC, Historical Papers / Communications historiques, 1957)
Keywords: Chemins de fer; Élections

Les p'tits chars d'autrefois - Massicotte, E.-Z. (Bulletin des recherches historiques, 1941)
Number: 10
Keywords: Tramways

Montreal Streetcars 651 Class - Binns, Richard M. (Canadian Rail, 1965)
Keywords: Tramways

Montreal Streetcars: 900 Class - Binns, Richard M. (Canadian Rail, 1965)
Keywords: Tramways

The Montreal and Southern Counties Railway - Murphy, M. Peter (Canadian Rail, 1981)
Keywords: Chemins de fer

Luther Holton: Mid-Century Montreal Railwayman - Klassen, Henry C. (Revue de l'Université d'Ottawa / University of Ottawa Quarterly, 1982)
issued: 1982-07/1982-09
Keywords: Chemins de fer; Holton; Luther Hamilton

La question des tramways à Montréal - Parenteau, Roland (L'Actualité économique, 1951)
issued: 1951-01/1951-03
Keywords: Tramways; Transport en commun

Effets du projet de canalisation du Saint-Laurent sur le port de Montréal - Camu, Pierre (L'Actualité économique, 1953)
issued: 1953-01/1953-03
Keywords: Navigation; Port; Voie maritime

Bonaventure Station Montreal - Worthen, Sanborn S. (Canadian Rail, 1976)
Keywords: Chemins de fer; Gare Bonaventure

Port Service Industries: the case of Montreal - Slack, Brian (Cahiers de géographie du Québec, 1982)
Number: 68
Keywords: Port

Building the Tramway Line over Mount Royal 1927 to 1929 - Telfer, Jim (Canadian Rail, 1980)
Keywords: Mont Royal; Tramways

L'incidence du développement autoroutier sur la croissance spatiale de l'agglomération montréalaise: 1950-1976 - Beaulac, Claude; Gabbour, Iskandar (Plan Canada, 1981)
Number: 3
Keywords: Autoroutes; Banlieue

Canada's Bid for the Traffic of the Middle West: A Quarter Century of the History of the St. Lawrence Waterway, 1849-1874 - Mckee, Samuel Jr. (Report of the Annual Meeting of the Canadian Historical Association / Rapports annuels de la Société historique du Canada, 1940)
Keywords: Navigation; Voie maritime

The Relationship between Transportation and Water Power on the Lachine Canal in the Nineteenth Century - McNally, Larry (Critical Issues in the History of Canadian Science, Technology and Medicine, 1983)
Keywords: Lachine (canal); Énergie hydraulique

Les Télécommunications à Montréal entre 1846 et 1946 - Canuel, Alain (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 1992)
Number: 1 (42)
Keywords: Bell Canada; Téléphone

The Engineers' Engineer: Sir John Kennedy and the Port of Montreal - White, Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Ingénieurs; Port

Train Country: an Illustrated History of Canadian National Railways - MacKay, Donald; Perry, Lorne (Douglas & McIntyre, 1994)
Keywords: Chemins de fer